2013
DOI: 10.1098/rsif.2012.0900
|View full text |Cite
|
Sign up to set email alerts
|

A fluid–structure interaction model to characterize bone cell stimulation in parallel-plate flow chamber systems

Abstract: Bone continuously adapts its internal structure to accommodate the functional demands of its mechanical environment and strain-induced flow of interstitial fluid is believed to be the primary mediator of mechanical stimuli to bone cells in vivo. In vitro investigations have shown that bone cells produce important biochemical signals in response to fluid flow applied using parallel-plate flow chamber (PPFC) systems. However, the exact mechanical stimulus experienced by the cells within these systems remains unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…More importantly, due to the high resolution of our local sub-scaffold FSI model, it was shown that the WSS was amplified significantly at the cell level when compared to the predicted WSS from the global model, with certain cases exhibiting a five-fold increase. Interestingly, similar cell level amplification effects of WSS have been observed for 2D cell perfusion systems (Anderson et al 2006;Vaughan et al 2013). However, in 2D cell perfusion systems, the WSS magnitudes to stimulate a biochemical response of cells in osteogenic and chondrogenic differentiation were much higher than the levels of WSS in our study.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…More importantly, due to the high resolution of our local sub-scaffold FSI model, it was shown that the WSS was amplified significantly at the cell level when compared to the predicted WSS from the global model, with certain cases exhibiting a five-fold increase. Interestingly, similar cell level amplification effects of WSS have been observed for 2D cell perfusion systems (Anderson et al 2006;Vaughan et al 2013). However, in 2D cell perfusion systems, the WSS magnitudes to stimulate a biochemical response of cells in osteogenic and chondrogenic differentiation were much higher than the levels of WSS in our study.…”
Section: Discussionsupporting
confidence: 52%
“…This approach allows deformable structures and resulting fluid flow fields to be predicted. By using the two-way FSI and multilevel methodologies, Vaughan et al (2013) predicted with high resolution flow fields and cellular deformation, and revealed the influence of WSS and fluid pressure on the bone cells that were cultured in a parallel-plate flow chamber system. Verbruggen et al (2013) applied a two-way FSI to precisely obtain the WSS and strain of the osteocytes in vivo environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies, the computational models of the devices for cellular mechanical stimulation have aimed for predicting the mechanical behavior of the device and quantifying the mechanical stimulation [17][18][19][20]. For instance, Thompson et al [17] developed a fluid structure interaction model for a commercial device (FX-4000) to quantify the fluid shear stress and biaxial mechanical strain of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [19] modeled a microfluidic platform of tunable microlens arrays (with a deformable PDMS cover) to generate mechanical strains on cells. Furthermore, Vaughan et al [20] characterized parallel-plate flow chamber systems, which utilised FSS to stimulate cells by a mutiscale fluid-structure interaction modeling approach. However, in this study, the computational model is developed not only for predicting mechanical behavior of the cell stretching device, but also for determining the elastic modulus of the material of the device (PDMS) by parametric variation study.…”
Section: Introductionmentioning
confidence: 99%